2011
DOI: 10.1016/j.jnoncrysol.2010.12.063
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium and chromium redox behavior in borosilicate nuclear waste glasses

Abstract: X-ray absorption spectroscopy (XAS) was used to characterize vanadium (V) and chromium (Cr) environments in low activity nuclear waste (LAW) glasses synthesized under a variety of redox conditions. V 2 O 5 was added to the melt to improve sulfur incorporation from the waste; however, at sufficiently high concentrations, V increased melt foaming, which lowered melt processing rates. Foaming may be reduced by varying the redox conditions of the melt, while small amounts of Cr are added to reduce melter refractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…The XANES data for all seven glasses (Fig.S1, red spectra) are nearly identical with respect to each other and are most similar to that for vanadinite. 5+ O 4 and V 4+ O 5 sites in each glass, as done earlier[25]. The fitting results indicate V 5+ O 4 tetrahedra in all glasses measured, with possible minor amounts (5 to 8 %) of V 4+ O 5 groups.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…The XANES data for all seven glasses (Fig.S1, red spectra) are nearly identical with respect to each other and are most similar to that for vanadinite. 5+ O 4 and V 4+ O 5 sites in each glass, as done earlier[25]. The fitting results indicate V 5+ O 4 tetrahedra in all glasses measured, with possible minor amounts (5 to 8 %) of V 4+ O 5 groups.…”
supporting
confidence: 73%
“…XANES data collected for the standards vary significantly from tetrahedral V 5+ O 4 in vanadinite to penta-coordinated V 4+ O 5 in cavansite (Fig. S1), and are nearly identical to the V XANES spectra of these compounds presented earlier [24][25][26][27]. The narrow edge feature near 5468 eV is most prominent for tetrahedral V 5+ in vanadinite, while the main edge shifts to lower energies for the more reduced penta-coordinated V 4+ in cavansite.…”
Section: Vanadium Xanessupporting
confidence: 53%
“…Chromium changes were very similar for all 3 LAW glasses; therefore, we only present the results of LAWB99 as an example (Figure C). It should be noted that the Cr in the glass may have Cr(III) and Cr(VI) coexisting, and the extracted Cr in the sodium sulfate salt is likely in the form of CrO42. Without measurable volatile loss, Cr is extracted into the salt after the first mixing and melting and remains stable in both phases.…”
Section: Resultsmentioning
confidence: 99%
“…XAS (X-ray Absorption Spectroscopy) studies of glass materials are numerously reported in the material sciences literature, covering such disparate applications as the investigation of historic artifacts (e.g., [6]) or geological specimen (e.g., [7]), characterization of optical glasses for solid state lasers (e.g., [8]) or the encapsulation of radiotoxic residues from nuclear fuel reprocessing (notably the work of McKeown et al [9][10][11][12][13][14][15][16]). These studies benefit from the ability of X-ray Absorption Fine Structure (XAFS) measurements to provide direct chemical speciation (e.g., determination of oxidation states and coordination geometries) through analysis of the Xray Absorption Near Edge Structure (XANES) -without the need for any sample pretreatment -while the Extended X-ray Absorption Fine Structure (EXAFS) reveals structural details on the local coordination environments (bond lengths, neighboring atom types) of glass matrix constituents -unlike standard X-ray Diffraction (XRD) analysis, which is severely hampered by the amorphous nature of elemental networks in glassy materials lacking any long range order.…”
Section: Introductionmentioning
confidence: 99%